Restorative Justice Sebagai Penyelesaian Perkara Pidana Berbasis Korban - Budi Sastra Panjaitan (Universitas Medan Area, 2022)
Restorative justice is the settlement of criminal cases based on victims. If the punishment for the perpetrator is still considered inadequate for the loss of the victim, then through restorative justice the rights of the victim in the context of the victim's recovery can be immediately carried out by the perpetrator directly, not by the state. The main issues discussed include: how to implement restorative justice at the level of investigation, prosecution and at trial in court, and how to resolve victim-based criminal cases between retributive justice and restorative justice. The research was conducted through normative legal research, the material studied was library material and the method of conclusion by deduction. Restorative justice at the level of investigation, prosecution and at the time of trial in court aims to protect the victim directly by the perpetrator and stop the investigation, investigation and or prosecution. Retributive justice tends to punish the perpetrator without considering the recovery of the victim, meanwhile restorative justice is the resolution of criminal disputes by means of restoring the victim.